Industry 4.0 and Turkey: A Financial Perspective - (:unkn) unknown (SPRINGER, 2018)
All sectors globally are going through a new industrial revolution which is called Industry 4.0. It is said to have a huge impact on manufacturing, lifestyle and future of people. Industry 4.0 demands a significant amount of investment in new technology. Major changes will have to take place in the global economy, because of migrating to Industry 4.0. The study aims to discuss Industry 4.0 and its influences on people, in an economic and financial perspective, in the world, particularly in Turkey.